Improving Community Digitalization Culture in Building Permits - Riau, Dwi Putranto; Pasaribu, Daniel (MIMBAR : Jurnal Sosial dan Pembangunan, 2024)
The readiness of the community to process building permits through SIMBG, which is all digital. The community is asked to finish it before submitting it to SIMBG. The digital transformation of municipal services has become a crucial aspect of innovative city initiatives, with the streamlining of building permit processing emerging as a critical focus area.This brings the community culture familiar with the digitization of permits.This study aims to know and analyze the cultural readiness of the community to obtain digital building permits through SIMBG.This study employed a descriptive qualitative methodology. The SIMBG operators that provided the primary and secondary data are taken from websites, journals, and technical service data. Qualitative data processing through interactive analysis is the study technique analysis that includes stages of data reduction, data display, and conclusion or verification drawing.This study's results indicate that the community's culture in digitizing building permits has shown an increase. This is indicated by only some people still taking care of building permits through SIMBG Clinic officers or offline and consulting on data input procedures and digital data requirements.  Increasing the culture of digitalization of building permits by the local government through Dissemination of Building Permit Regulations regarding e-government Applications; Improving the Competence of Human Resources and the business world in Information Technology; Increasing the reach of the internet in all corners of the country; and Repair and update the SIMBG Application.